Punishing schools : fear and citizenship in American public education - Lyons, William, 1960- (Law, meaning, and violence., 2006)
Argues that our educational system has become both the subject of legislative punishment and an instrument for the punishment of children. Lyons and Drew analyze the connections between state sanctions against our schools (the diversion of funding to charter schools, imposition of unfunded mandates, and enforcement of dubious forms of teacher accountability) and the schools' own infliction of punitive measures on their students--a vicious cycle that creates fear and encourages the development of passive and dependent citizens. - from publisher information.